Physicochemical properties and bioactive compounds content in encapsulated freeze-dried powders obtained from blueberry, elderberry, blackcurrant and maqui berry - Busso Casati, Carolina (2019)
Fil: Busso Casati, Carolina. Universidad Católica Argentina. Facultad de Ciencias Agrarias; Argentina